Republic of Honduras : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This Country Financial Accountability Assessment (CFAA) aims to assist the Government implement effective measures to strengthen public financial management, which would result in more effective economic development, and poverty reduction programs. While the implementation of the integrated financial management system has improved the Government's ability to control, and manage expenditure, weak internal controls, and internal audit capacity in spending agencies hinder the assurance of efficiency and certification of expenditures. The report finds fiscal responsibilities are not managed by the Treasury, but rather by the Office of Public Credit, and the Central Bank, a dispersion of responsibility for the management of public funds which results in functional gaps, directly affecting the security, and control of Government funds. And, while tax administration is improving, the procedures governing tax collections are still weak, consequently, with no proper reconciliation between the funds paid by the taxpayers, to that of the funds declared by banks as collected, and, there is no reconciliation between the funds received by the banks, and those transferred to the treasury accounts. Furthermore, the external audit function is still evolving, following the creation of the new Audit Court, for which the Government has been supporting a capacity-building program. However, the lack of external audits of the Government's financial statements represents a weakness in the transparency of public finances. The CFAA suggests as the most urgent need, to upgrade the quality of human resources in the public sector. In particular, efforts need to focus on strengthening of the legal, and accountability framework for public financial management, upgrading and modernizing Government financial management, and administration systems, streamlining processes and procedures, and, rationalizing and strengthening institutions responsible for ensuring accountability.